Performance of asphalt rubber mixtures - Thives, Liseane Padilha (2010)
Asphalt rubber mixtures are one of the most promising techniques to extend the service life of asphalt pavement overlays. Asphalt rubber binder is composed of crumb rubber from reclaimed tires and conventional asphalt. The asphalt rubber binder can be obtained through wet process in two different systems: terminal blending (produced at industrial plants) and continuous blending (produced in asphalt plants). This study presents a laboratory evaluation of asphalt rubber mixtures produced with different asphalt rubber binders, using gap and dense gradations. The mechanical behavior of the mixtures studied was established through several laboratory tests (stiffness, fatigue cracking and permanent deformation). A finite-element methodology was also employed to evaluate the fatigue life in terms of reflective cracking. Moreover, the morphologies of the crumb rubber and of the asphalt rubber binder were analyzed through scanning micrographs. The rheology of the asphalt rubber binder was characterized in order to predict the mechanical behavior of asphalt rubber mixtures. This study indicates that asphalt rubber mixtures improve the mechanical properties of asphalt pavements, enhancing their performance and increasing the service life of overlays in comparison to conventional mixtures.